Impaired recollection-based episodic memory as a cognitive endophenotype in schizophrenia. Issue 8 (13th September 2020) - Abhishek, Priyadarshee; Nizamie, S Haque; Jahan, Masroor; Kumar, Devvarta; Goyal, Nishant; Pachori, Hariom; Katshu, Mohammad Zia Ul Haq
ABSTRACT: Introduction: Patients with schizophrenia show impaired recollection but largely preserved familiarity-based episodic memory. This study was done to clarify the endophenotypic nature of recollection and familiarity-based episodic memory in schizophrenia and the role of emotional valence of memoranda and degree of recall confidence in it. Method: Twenty-five patients with schizophrenia, one unaffected sibling of each patient, and twenty-three healthy controls completed two tasks assessing recollection and familiarity-based processes in episodic memory. In the first task, participants were asked to remember positive, negative, and neutral emotional valence words in a remember–know paradigm. In the second task, in addition to recollection and familiarity-based responses, participants were asked to make confidence judgments about their responses. Results: Patients with schizophrenia and their first-degree relatives (FDRs) performed poorly on recollection but not familiarity-based responses, compared to healthy controls; performance of first-degree relatives was in between and significantly different from that of both patients and controls. The differences in recollection and familiarity-based responses across the three groups were not moderated by recall confidence judgments or emotional valence of memoranda. Furthermore, there was no correlation between recollection-based memory impairments and duration or severity of illness or current medication exposure. Conclusions: Impaired recollection-based memory constitutes a potential cognitive endophenotype in schizophrenia. Furthermore, selective impairment of recollection-based, but sparing of familiarity-based, memory in patients and their FDRs supports the distinct nature of recollection and familiarity-based episodic memories.